Variation in Species Composition and Diversity of Burnt and Unburnt Forest of Shorea robusta - Godar, Prakash; Chettri, Mukesh Kumar; Chaulagain, Bidur Prasad; Joshi, Giri Prasad; Aryal, Biva (Nepalese Journal of Agricultural Sciences, 2026)
Forest fire is a critical ecological process that influences species composition, diversity, and regeneration dynamics. This study analyzes the impact of forest fire on the species composition and diversity of Shorea robusta forests in the Chure region of Butwal, Nepal, by comparing burnt and unburnt sites. Burnt areas were identified using historical fire data from ICIMOD and the Department of Forests and Environment. Vegetation was sampled using a systematic random method with 60 circular plots of 10 m, 5 m, and 1 m radii for trees, shrubs, and herbs, respectively. The burnt forest was co-dominated by Shorea robusta and Lagerstroemia parviflora, with associates including Terminalia alata and Careya arborea. In contrast, the unburnt forest was dominated by S. robusta and Anogeissus latifolia, associated with species like Tectona grandis and Mallotus philippensis. The Shannon-Wiener diversity and Margalef's richness indices were higher in the unburnt forest. However, the average density of S. robusta was significantly greater in the burnt forest. The findings suggest that fire plays an essential role in shaping species composition and promoting the density of Shorea in these forests, despite a reduction in overall diversity.